A proposed feasible classification of common bile duct duplications based on a newly described variant and review of existing literature - Huixue Sheng; Guiling Chen; Ming Yang; Hongmei Guan (BMC, 2022)
Abstract Background Duplication of the common bile duct (CBD) is extremely rare among the anatomical variations in the biliary tract system, which presents a septum within the CBD or an accessory CBD. In our study, we report a rare case of duplication of the common bile duct combined congenital biliary dilatation.we present a rare case of a septum in the dilated biliary tract. Case presentation We reported a 5-year-old Asian girl who had history of repeated abdominal pain for 4 days and aggravated for 1 day. Magnetic resonance cholangiopancreatography (MRCP) examination revealed duplicated common bile duct (DCBD) malformation with congenital biliary dilatation and distal cholelithiasis. The patient underwent choledochal cyst resection and biliary tract reconstruction and abdominal cavity irrigation and drainage under general anesthesia. A septum was found within the common bile duct during the operation. The septum divided the extrahepatic bile duct into two parts connected to the left and right hepatic ducts respectively and the gallbladder is attached to the repeated right bile duct which was not previously reported in the literature. Conclusions We complement and adjust the classification of common bile duct duplication by reviewing the literature.